A Comparative Study of Abraham Geiger and Al-Aṣfahānī on the Concept of Rabb - Az Zahra, Priyantika Lesyaina; Mansur, Syafiin; Millah, Mus’idul (Prodi Studi Agama-Agama, 2026)
Rabb is one of the central terms in the Qur’an that encompasses complex linguistic, semantic, and theological dimensions. This study aims to analyze and compare the views of Abraham Geiger and Al-Raghib al-Aṣfahānī regarding the concept of Rabb, while also examining the epistemological frameworks underlying their interpretations. This research employs a qualitative method with a comparative-analytical library research approach. The theoretical framework applied in this study is Hans-Georg Gadamer’s hermeneutics, particularly the concept of fusion of horizons in textual interpretation. The primary sources include Al-Aṣfahānī’s Al-Mufradāt fī Gharīb al-Qur’ān, Abraham Geiger’s Judaism and Islam, and Was hat Mohammed aus dem Judenthume aufgenommen?. The findings reveal that although both scholars depart from relatively similar etymological roots, they arrive at different understandings of the concept of Rabb. Al-Aṣfahānī interprets Rabb within the framework of Islamic theology as a divine concept related to tarbiyah, sustenance, and the absolute sovereignty of God. In contrast, Geiger approaches Rabb through a historical-comparative perspective, viewing it as a term shaped within Jewish rabbinic and broader Semitic traditions. These differences demonstrate that interpretations of the concept of Rabb are strongly influenced by intellectual traditions, historical backgrounds, and the pre-understandings of each interpreter